Optimalisasi Sosial Media untuk Pengembangan Usaha BUMDes Dasa Warsa Desa Waru Barat Pamekasan - Olivia, Rizma; Nugroho, Taufik Rizal Dwi Adi; Selvia, Erika; Nisak, Hoirun; Putra, Rafly Mahendra; Anggraini, Rizky Dwi; Marista, Tri Lestari (Jurnal Ilmiah Pangabdhi, 2023)
West Waru Village BUMDes was founded in 2017 in accordance with Village Regulation no 3 of 2022 concerning the Establishment of a Village-Owned Enterprise with the name BUMDes Dasa Warsa and has a certified legal entity. The method for implementing community cervice acitivities conducted at BUMDes Dasa Warsa, West Waru Village, Waru District, Pamekasan Regency is carried out by following the working hours of BUMDes staff in assisting the implementation of digital marketing and optimizing social media. Currently, BUMDes Dasa Warsa has 5 managed business units, namely livestock, ISP (Internet Service Provider), TPS3R, tourism and cafes. The development and construction of units at Dasa Warsa BUMDes has been planned for the following years. The social media optimization activities that have been carried out have proven to be effective and have had a good impact on product marketing in BUMDes business units. sales have increased and profits have been made, it can be seen that the content planning strategy on social media Instagram really helps interact with consumers and helps people get to know the products offered by BUMDes Dasa Warsa.